Human Labour Supply: A Necessary Evil? - Samaranayake, D. I. J. (Asian Development Policy Review, 2017)
Study concludes how the human labour supply appears to be a cost but a necessary component. Observations are made through comparative literature and evidences emerged over patterns and symmetries in the middle of orthodox and heterodox discourses of labour-leisure dichotomy. Analysis reveals that the tradeoffs between leisure with various types of labour supply appear as a cost, simply an evil which can reduce leisure, comfort of people or profits of a firm. In terms of human capital formation; having full time higher education generates ‘Twin Cost’ on graduate employee. As in Buddhist economics ideology, there is a complementary relationship between work and leisure. Creating a better surface for work can reduce some level of cost of workers. Along with Marxist viewpoint on labour supply, since there is a surplus value for labour, it may generate a cost for the workers. Somehow new technological development may create some freedom for workers while utilizing the dead labour. However, along with futuristic ideology, an advanced society with an intensity to zero labour supply with robotics replacements, human beings are going to be deceased; not in terms of their lives but due to termination of their values in future.